Perioperative Assessment in Cancer Patients: A Systematic Review of Existing Domains and Practices - Restuwati Restuwati; Ika Yuni Widyawati; Laily Hidayati; Richal Grace Zefanya Uly (Indonesian Journal of Global Health Research, 2026)
Perioperative assessment is essential to optimize surgical outcomes and reduce complications, especially in cancer patients who often have complex clinical conditions. This systematic review aims to provide an overview of existing domains and practices in perioperative assessment specific to cancer patients. A systematic search was conducted in databases including ScienceDirect, Scopus, PubMed, and Google Scholar, identifying 1,071 articles. After removing 384 duplicates, 687 articles underwent title and abstract screening, leading to the exclusion of 980 articles. Forty-five full-text articles were reviewed for eligibility; 16 were excluded due to inaccessibility, resulting in 12 articles included in the final analysis. Data were synthesized descriptively to identify common assessment domains and practices. The review found several key domains commonly assessed perioperatively in cancer patients, such as nutritional status, frailty, psychological health, cardiopulmonary function, and immunological parameters. However, there is notable variability in the instruments and methods used across studies, indicating a lack of standardized assessment protocols. Comprehensive perioperative evaluations that integrate these domains may enhance surgical planning and risk prediction in oncology patients. While multiple domains are recognized as important in perioperative cancer assessment, standardized and integrated approaches remain limited. Addressing these gaps could improve risk stratification and patient outcomes, although challenges like tool inconsistency, interdisciplinary coordination, and resource availability must be overcome.